Product Design Evaluation of Scooter 2 Pedal with Quality Function Development Method - Rozi Saferi; Asmara Yanto; Muhammad Ilhamdi (Jurnal Teknik Mesin, 2021)
A scooter is defined as a two-wheeled vehicle with a step-through chassis and footrest platform. There are several factors that must be considered in planning and designing this scooter including an attractive design, selection of the right material, analysis of material strength, ergonomics factors and others. The purpose of this research is to design a 2 pedal scooter and evaluate the design results using the quality function development (QFD) method. The results of the evaluation of the 2-pedal scooter product design with the quality function development method show that the highest stress occurs at a load of 90 kg with a displacement of 6.11 mm and is still safe to use. Furthermore, the design of the 2-pedal Scooter is better than otoped in terms of the transmission system and ergonomics and is better than commercial scooters in terms of weight.